On the emergence of descriptive norms. (February 2014) - Muldoon, Ryan; Lisciandra, Chiara; Bicchieri, Cristina; Hartmann, Stephan; Sprenger, Jan
A descriptive norm is a behavioral rule that individuals follow when their empirical expectations of others following the same rule are met. We aim to provide an account of the emergence of descriptive norms by first looking at a simple case, that of the standing ovation. We examine the structure of a standing ovation, and show it can be generalized to describe the emergence of a wide range of descriptive norms.